Improved Algebraic Cryptanalysis of the Reduced-Round Advanced Encryption Standard - Rezaeipour, Davood (2011)
As we know Cryptology is divided into two parts: “Cryptography” and “Cryptanalysis”. Since block ciphers can be deployed in many different applications, so we focus on Advanced Encryption Standard (AES) which is the successor of Data Encryption Standard (DES). In cryptography, we purpose new block cipher (NBC08) in order to understand the inner structure and other known properties. NBC08 accepts an variable-length key up to 512 bits, which is an improved security/performance tradeoff over existing block ciphers. It cannot be analyzed by known cryptanalytic attacks. We study AES specifications and also the algebraic structure for AES over Galois Fields GF(2) and GF(28). We describe the most common cryptanalytic techniques on block ciphers, such as Differential, Linear and Integral cryptanalysis. We study the different solving methods for system of equations of AES in both fields, GF(2) and GF(28). The process of performing these methods on AES acts as Algebraic attack. In cryptanalysis, we improve the algebraic cryptanalysis attack on the reduced-round AES. It’s called Ground Algebraic attack. The notable property of Ground attack is that less requirements to any information for analyzing AES. Ground Algebraic attack is the first attack on reduced-round AES which can break 4-round and 5- round AES by respectively 256 and 2113.5 computational complexities. The number of required chosen plaintexts for cryptanalysis 4-round and 5-round AES is 8 and 15,respectively.